Photocatalytic degradation of rhodamine B by Eu-doped BiOI nanobelts induced by visible radiation - Prakasit Intaphong (2020)
© 2019, Australian Ceramic Society. Pure bismuth oxyiodide (BiOI) and Eu-doped BiOI samples with different contents of Eu dopant as visible-light-driven photocatalysts were prepared by a sonochemical method. The as-synthesized samples were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED), and X-ray photoelectron spectroscopy (XPS). In this research, tetragonal BiOI nanobelts were obtained for 1 wt% Eu dopant and an additional phase of orthorhombic Bi5IO7 was detected for doping with 5 wt% and 10 wt% Eu. Thus, the limited content of Eu in BiOI lattice is 1 wt%. The activity of the as-prepared samples was evaluated through the photodegradation of rhodamine B (RhB) under visible radiation, and 1 wt% Eu-doped BiOI nanobelts exhibited the best photocatalytic activity of 98.4% within 240 min. The photodegradation mechanism of RhB by Eu-doped BiOI was also discussed.